Study of Artisanal Açaí Beater under the Light of Institutionalist Theory: An Integrative Review (Global Journal of Management and Business Research, 2023)
In the North region of Brazil, the economic and social significance of the artisanal açaí whisking activity cannot be contested, a reality that instigates research. In this context, the objective of studying and better knowing the activity of the scout under the precepts of the Institutionalist Theory emerged. In order to reach the established purpose, an Exploratory Research type was adopted with a bias of Integrative Review of the theoretical framework underlying the Institutionalist Theory. As a result, it is understood that it is possible to infer that the Institutionalist Theory and its evolution makes it possible to homogeneously support not only studies focused on objects in the form of companies, enterprises, organizations and correlates, thus generating a framework and, as a consequence, common deliverables for each object.
Keywords: institutionalist theory; integrative review; handmade acai whisk